2015
DOI: 10.1016/s1474-4422(15)00008-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral globus pallidus stimulation for severe Tourette's syndrome: a double-blind, randomised crossover trial

Abstract: UK National Health Service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 32 publications
6
100
0
4
Order By: Relevance
“…Additionally, it is documented that the rate of infection of DBS hardware seems increased in patients with GTS patients 167,168 . Whether this is due to tic-related behaviours and comorbidity (e.g., picking at wound), or distinct immunological profiles remains unclear 168 .…”
Section: Thoughts For Dougmentioning
confidence: 99%
“…Additionally, it is documented that the rate of infection of DBS hardware seems increased in patients with GTS patients 167,168 . Whether this is due to tic-related behaviours and comorbidity (e.g., picking at wound), or distinct immunological profiles remains unclear 168 .…”
Section: Thoughts For Dougmentioning
confidence: 99%
“…Within this context of target choice, one should mind the existing interdependence between symptoms and also the complex interconnection between the various nuclei (Saleh et al 2012). The largest experience comes from thalamic and pallidal DBS, which appear the most promising targets Wardell et al 2015;Kefalopoulou et al 2015;Ackermans et al 2011;Welter et al 2008). At our institution, we have a medication-guided DBS approach.…”
Section: Discussionmentioning
confidence: 99%
“…1). Based on double-blind studies the most robust and promising data comes from thalamic and pallidal stimulation (Ackermans et al 2011;Kefalopoulou et al 2015). Despite promising results (Saleh et al 2012;Servello et al 2015 • 2012: Canada (Steeves et al 2012).…”
Section: Neurosurgery In Tsmentioning
confidence: 99%
“…There have been randomized, double-blind trials of Centromedian/parafascicular (CM-Pfc) thalamic DBS [82][83][84] as well as DBS within the GPi [84,85], with accompanying improvement in quality of life. Of these, one small trial compared bilateral stimulation of the CM-Pfc, the anteromedial GPi, both targets combined, and sham stimulation, and found that the anteromedial GPi was the most effective target for stimulation in all 3 Tourette's patients treated [84].…”
Section: Experimental Uses Of Dbs In Movement Disordersmentioning
confidence: 99%